The relationship between body mass index and cerebrospinal fluid pressure in children with pseudotumor cerebri - Yakup Çağ; Safiye Güneş Sağer; Merve Akçay; İsmail Kaytan; Elif Söbü; Aydan Erdem; Yasemin Akın (BMC, 2024)
Abstract Background Childhood obesity has become a major global health problem. Obesity is associated with major health problems, such as diabetes, hypertension, dyslipidemia, cardiovascular disease. Obesity is also considered a risk factor for Pseudotumor cerebri (PTC). The present study aimed to investigate the relationship between body mass index (BMI), and cerebrospinal fluid (CSF) pressure in patients with pseudotumor cerebri. Methods A total of 48 children diagnosed with PTC, who were aged < 18 years and followed up in the pediatric clinic were included in the retrospective study. National BMI percentile curves were used for reference. We investigated statistically the relationship between BMI, clinical and laboratory results, and CSF pressure in patients. Results Of total patients 27 were female (56.25%) and 21 were male (43.75%). With regard to the BMI percentile, 20 (41.67%) were overweight or obese. CSF pressure was higher in overweight and obese patients compared to children with BMI in normal ranges (p < 0.05). A statistically significant positive correlation was also observed between BMI and CSF pressure values and between monocyte and CSF values (p < 0.05). Conclusions The results of the present study indicate a direct relationship between CSF pressure and BMI in children with PTC. Appropriate diet, exercise, and medical treatment in overweight and obese children can make a significant contribution to the treatment of PTC. Additionally, a significant correlation was observed between CSF pressure and monocyte levels.